Company perception on practical training: a case study of Computer Science students UiTM Perak, Tapah Campus / N. R. Nik Mustapha ... [et al.] - Nik Mustapha, N. R.; Jamian, N. H.; Ali, N. A.; Md Saleh, S. S. (UiTM Press, 2018)
Practical training is one of the platforms used to expose students to the real working environment so that they will be ready when they graduate. The objective of this study is to investigate companies' perception on skills performance in terms of Interpersonal Skills, Communication Skills, Intellectual Skills, Initiative Taking, Job Attitude, Personal Efficiency and Leadership Skills. Data were collected based on supervisors' evaluation of the performance of 113 undergraduate students majoring in Computer Sciences (CS110) at UiTM Perak, Tapah Campus who attended Practical Training from 2016 until 2017. The skills performance were built upon the faculty's programme outcomes. The result indicate that there were difference in the items score between company expectations and observations marks related to skills performance.